(3eYQaI NhGU CSeGA Gddg GdMSfis - (3LdGd GdOjfs
(3ChdgG (B:s
(3gPg eYQaI NhGU Gddg GdMSfi hgj JSYI hJSYhf ESekG gh Gddg GdPi dG Edg EdG gh YGde GdZjH hGdTgGOI ef bQCgG cd jhe Cda eQI LYdg Gddg JbjkG ef Cgd Gdjbjf s
(3BNQgG (B:s
(3jG HOjY cd ef bQC gPG GdGSe eGFI eQI bHd WdhY GdTeS de jUH LSOg Cde aEf Gddg JYGdi jUHQg hjYGajg hjTajg JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdJGSYs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9276) s
Keywords: (3GdJhMjO hGdedd hGdfMds